Analisis Gambaran Peradaban Masyarakat Suku Lembak Bengkulu yang Tinggal di Sungai Cho Malaysia - Wani, Gytami; Safrianto, Sendy; Jannah, Miftahul; Qonita Salsabila, Rahma; Fitri Santiya, Riska; Kurniawan, Dimas; Fadhillah, Riska (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the civilization of the Lembak Tribe community from Bengkulu, who reside in Sungai Choh, Malaysia. The Lembak Tribe, with a migration history of more than three decades, has formed a close-knit community in Sungai Choh, as well as in Berang and Gemas. This study highlights how they have maintained their cultural, religious, and social identities within the context of diaspora, and how interaction with local Malaysian culture has influenced the transformation of their identity. The research employed qualitative methods, including interviews, observations, and literature studies. The results show that, despite elements of acculturation, the Lembak community in Sungai Choh has successfully preserved many of their traditional elements. Support from organizations such as the Bengkulu Association of Malaysia has also played a significant role in the continuity of this culture. This article is expected to provide broader insights into the cultural and identity dynamics among migrant communities.